2016
DOI: 10.1016/j.athoracsur.2016.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Extracorporeal Bypass in Minimally Invasive Heart Valve Operations: A Prospective Randomized Trial

Abstract: The intraprocedural data were excellent and comparable in the groups, but postoperative outcomes were better in the MECC group. Thus MECC is preferable to CECC even for minimally invasive valve procedures. These findings strongly support a combined strategy of minimally invasive valve operations and minimally invasive extracorporeal circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…TNF‐α has an early peak and decreases within 90 min after the triggering incident. The levels did not vary over time in both groups, which are in contrast with clinical trials for CABG and valve surgery . In both corresponding trials, MiECC showed the main advantages over CECC at the end of CPB or in the first hour postoperatively.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…TNF‐α has an early peak and decreases within 90 min after the triggering incident. The levels did not vary over time in both groups, which are in contrast with clinical trials for CABG and valve surgery . In both corresponding trials, MiECC showed the main advantages over CECC at the end of CPB or in the first hour postoperatively.…”
Section: Discussionmentioning
confidence: 61%
“…Clinical trials comparing CECC with MiECC (type III and IV) in SAVR showed that MiECC systems are a viable alternative to CECC. MiECC type III showed optimal myocardial protection, reduced inflammatory reaction, and a shorter intensive care unit stay . In a parallel clinical trial of our group, the neurological event rate was lower compared with CECC by using a type II MiECC .…”
mentioning
confidence: 63%
“…In 400 patients undergoing elective CABG randomised either to conventional CPB or to MiECC, the latter group required significantly less ABT (Remadi et al, ). Smaller randomised trials have yielded similar results in CABG (Abdel Aal et al, ), isolated aortic valve replacement (Castiglioni et al, ) and mitral or aortic valve procedures (Baumbach et al, ). A prospective observational study by Immer et al .…”
Section: Resultsmentioning
confidence: 89%
“…In 400 patients undergoing elective CABG randomised either to conventional CPB or to MiECC, the latter group required significantly less ABT (Remadi et al, 2006). Smaller randomised trials have yielded similar results in CABG (Abdel Aal et al, 2011), isolated aortic valve replacement (Castiglioni et al, 2007) and mitral or aortic valve procedures (Baumbach et al, 2016). A prospective observational study by Immer et al (2007), including more than 1000 CABG patients, found that the number of patients exposed to transfusion, as well as the number of units transfused per patient, was significantly lower in the MiECC group.…”
Section: Cardiopulmonary Bypass Strategymentioning
confidence: 99%
“…However, Baumbach, et al and Wang, et al reported a superior outcome of MECC in a population of valve surgery. (21,16) It should also be borne in mind that with MECC there is no back-up of a cardiotomy sucker to collect spilled blood in the chest back to the circulation. All blood gets sucked away to the cell saver, where plasma (clotting factors) and platelets are washed out.…”
Section: Minimal Extracorporeal Circulationmentioning
confidence: 99%